ANALYSIS OF MATERIAL LOSS DUE TO FLOOD DISASTER IN THE SUB-DISTRICT OF SILAT HULU, KAPUAS HULU REGENCY - Holifah Nurfitri; Florensia Rintia; Francista Francista; Ayu Rianingsih; Nurul Ramdhania; Ajun Purwanto; Dony Andrasmoro; Eviliyanto Eviliyanto (Universitas Sebelas Maret (UNS), 2023)
A flood is a frequent disaster during the rainy season and causes many losses, good materials, treasure objects, and casualties. The study aims to know the loss of materials caused by disasters that flood Bandang in the Silat Hulu Sub-district. The method of research used is descriptive quantitative. Collected data is secondary data, including damaged buildings, facilities and infrastructure, and land. The method analysis used is descriptive. The study results show that The Silat Hulu Sub-district experienced twice the floods successively. The first occurred on 18-19 October 2021 and 22-23 October 2021. A total of 11 villages of 14 villages experience a flood. Consequently, the flood and loss of materials, including dozens of house inhabitants of Village Selangkai and Entebi, were damaged, collapsed, and swept away. A total of 1,813 families were evacuated, and the total loss consequence flood around Rp. 20,000,000.00-30,000,000.00.